Effect of inorganic phosphate and benzyl thiocyanate on the activity of anhydrotetracyline oxygenase in Streptomyces aureofaciens - Bĕhal, V; Grégrová-Prusáková, J; Hostálek, Z (Folia microbiologica, 1982)
The level of anhydrotetracyline oxygenase (an enzyme catalyzing the penultimate reaction in the biosynthesis of tetracyline) in Streptomyces aureofaciens was substantially influenced by the amount of inorganic phosphate and by the presence of benzyl thiocyanate in the cultivation medium. Phosphate decreased the specific activity of the enzyme, particularly when added to a growing culture. On the other hand, benzyl thiocyanate increased the specific activity of the enzyme. Its effect was most conspicuous in the growth phase. The effect of benzyl thiocyanate was more pronounced in the low-production strain than in the producing variant. Inorganic phosphate and benzyl thiocyanate did not influence the enzyme activity in vitro. Phosphate added to the growing cultures was readily absorbed by the cells. During this time the enzyme synthesis was repressed, derepresion occurred only after exhaustion of phosphate from the medium. The stimulatory effect of benzyl thiocyanate on the enzyme synthesis was not reversed by the inorganic phosphate added.
Keywords: thiokyanatany; tetracykliny; Phosphates; Tetracyclines; oxygenasy; fosfáty; Thiocyanates; Streptomyces; Oxygenases